1996
DOI: 10.1139/o96-061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the interaction of motuporin and microcystins with type-1 and type-2A protein phosphatases

Abstract: Heptapeptide microcystin and pentapeptide motuporin (nodularin-V) are equipotent inhibitors of type-1 and type-2A protein phosphatase catalytic subunits (PP-1c and PP-2Ac). Herein we describe elucidation of the molecular mechanisms involved in the interaction of these structurally similar hepatotoxins with PP-1c/PP-2Ac and identification of an important functional difference between their mode of interaction with these enzymes. Microcystin-LR, microcystin-LA, and microcystin-LL were found to interact with PP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 30 publications
7
121
2
2
Order By: Relevance
“…Although motuporin contains valine instead of the arginine in nodularin, these compounds are equipotent inhibitors of PP1 and PP2A (Craig et al 1996). The results are consistent with the report that the arginine residue in microcystin-LR does not significantly contribute to biological activity, based on a comparison of enzyme inhibition and receptor binding activity ).…”
Section: Nodularinsupporting
confidence: 90%
See 1 more Smart Citation
“…Although motuporin contains valine instead of the arginine in nodularin, these compounds are equipotent inhibitors of PP1 and PP2A (Craig et al 1996). The results are consistent with the report that the arginine residue in microcystin-LR does not significantly contribute to biological activity, based on a comparison of enzyme inhibition and receptor binding activity ).…”
Section: Nodularinsupporting
confidence: 90%
“…Sponges of the order Haplosclerida often contain 3-alkylpyridinium salts (Andersen et al 1996;Sep i 2000), some of which were reported to be toxic to mammals. The first example of this class is halitoxin (29) isolated from Haliclona spp.…”
Section: Polyalkylpyridiniumsmentioning
confidence: 99%
“…Second, part of the MC-LR may covalently bind with protein phosphatases in liver and then released gradually over time. Covalent binding of MCs with protein phosphatases reduces extractability of microcystins (Craig et al 1996), which could result in an underestimation of the amount of toxin really present into the liver (Malbrouck et al 2004). Although the mechanism of sustainedrelease behavior of MC-LR is not well studied so far, the binding form and subsequent release may account for the fluctuation of MC-LR detected in the rat liver during the experimental process.…”
Section: Fig 2 Esi Lc/ms/ms Analysis Of Mc-lr and Its Two Metabolitementioning
confidence: 99%
“…Indeed, MCs can covalently bind to various proteins (Craig et al, 1996;Gehringer et al, 2004). However, our investigation of the accumulation of MCs in these two gastropods used ELISA methods, which detects only free forms of MCs (Hastie et al, 2005;Maynes et al, 2006).…”
Section: Potential Risk To Human Healthmentioning
confidence: 99%